Infanticide by Adult Females Causes Sexual Conflict in a Female-Dominated Social Mammal - East, Marion L.; Thierer, Dagmar; Benhaiem, Sarah; Metzger, Sonja; Hofer, Heribert (Frontiers in Ecology and Evolution, 2022)
^Infanticide by adult females includes any substantial contribution to the demise of young and inevitably imposes fitness costs on the victim’s genetic fathers, thereby generating sexual conflict with them. Few if any studies have quantified the impact of infanticide by females on male reproductive success, the magnitude of sexual conflict this causes and possible counterstrategies males use against infanticidal females. We examine these topics in spotted hyena (Crocuta crocuta) clans, where females socially dominate breeding males and strong female mate-choice is independent of male social status. We consider two causes of infanticide by females, violent attacks on cubs and fatal maternal neglect. Violent attacks are predicted during periods of social instability at the top of the female linear dominance hierarchy and victims are expected to predominantly have mothers above median rank. Fatal maternal neglect, when starving litters are abandoned, is associated with monopolization of food in clan territories by high-ranking females, and victims are predicted to have mothers below median rank. Female perpetrators of violent attacks are expected to reduce the reproductive success of the fathers of their victims more than perpetrators of fatal maternal neglect. We tested these predictions using 30+ years of data (54 recorded violent attacks, 43 cases of fatal maternal neglect, DNA profiling of 1671 individuals). Using long-term observations at communal dens we investigated whether males use counterstrategies against infanticide reported in other mammals. Due to female social dominance over breeding males, strong female mate-choice and prolonged offspring dependence on lactation in spotted hyenas, we predicted that these counterstrategies were unlikely to be used by males against females, thus no incidences of them were likely to be observed. Our results revealed that breeding males lost cubs to violent attacks at all stages of their reproductive tenure and to perpetrators with whom they did not sire offspring. Amongst known sources of paternity loss, violent attacks comprised 12.2 % and maternal neglect 9.8 % of cases. Violent attacks significantly reduced offspring production rates of breeding males, suggesting that infanticide by females generates sexual conflict. As predicted, no evidence of males using counterstrategies against infanticide by females were observed.